Letter (copy) : Spain - Citrine, Walter, 1887-1983
011-0089-001 WMC/WJB/AC/727 Sit. Esp. 176 International 10th May, 1937. Mr. W. Schevenels, International Federation of Trade Unions, 9, avenue d'Orsay, PARIS VIIe Dear Comrade Schevenels, SPAIN. In reply to your circular letter of 26th April, in which you ask us for information ebout our action in regard to Spain, as you will see from the enclosed manifesto, we made special reference in it to the conflict. This was followed by demonstrations and meetings of Unions and Labour Parties and other organisations in the principal towns, the largest demonstrations being that held in Hyde Park, London, on Sunday, May 2, where more than 30,000 people were present. Addresses were given by Trade Union leaders and Labour Members of Parliament. In addition to these meetings members of the Labour Party have been drawing public attention to various aspects of the conflict by speeches and Questions in the House of Commons. Special reference was made to the bombing of Guernica, and you will have gathered from the papers that on May 6 last, our Foreign Secretary stated that the British Government would be quite willing for an impartial enquiry to be held. The T.U.C. also decided to do all it could to help in the work of caring for the children who are being evacuated from Bilbao, and issued a special appeal for assistance. Yours faithfully, General Secretary 292/946/11/89